Hypochloraemia and 30 day readmission rate in patients with acute decompensated heart failure - Roman Marchenko; Adam Sigal; Thomas E. Wasser; Jessica Reyer; Jared Green; Christopher Mercogliano; Muhammad Sohail Khan; Anthony A. Donato (ESC Heart Failure)
Abstract Aims Despite recent advances in guideline‐directed therapy, rehospitalization rates for acute decompensated heart failure (ADHF) remain high. Recently published studies demonstrated the emerging role of hypochloraemia as a predictor of poor outcomes in patients with ADHF. This study sought to determine the correlation between low serum chloride and 30 day hospital readmission in patients with ADHF. Methods and results We retrospectively reviewed electronic medical records of 1504 patients who were admitted to one 700 bed US tertiary care centre with the diagnosis of ADHF between June 2013 and December 2014. Of the 1504 reviewed records, 1241 were selected for further analysis. Hypochloraemia (either on admission or at discharge) was identified in 289 patients (23.3%) and was associated with significantly higher 30 day hospital readmission rate or death (42.2% vs. 33.7%, P = 0.008). This association persisted in multivariate analysis when controlling for serum sodium, weight loss, diuretic dose, adjunct thiazide use, serum blood urea nitrogen, and BNP levels (OR: 1.35, 95% CI: 1.02–1.77, P = 0.033); however, the predictive value of the overall model was low (Naglkerke R2 = 0.040). Hypochloraemia was also found to be associated with increased 12 month mortality in our cohort (31.4% vs. 20.2%, P = 0.015) that correlates with the results of previously published studies. Conclusions Low serum chloride measured in patients admitted for ADHF is independently but weakly associated with increased 30 day readmission rate and demonstrated low predictive value as a potential biomarker in this cohort.